High‐Indexed PtNi Alloy Skin Spiraled on Pd Nanowires for Highly Efficient Oxygen Reduction Reaction Catalysis. Issue 17 (28th March 2019) - Zhao, Yueping; Tao, Lu; Dang, Wei; Wang, Linlin; Xia, Meirong; Wang, Bo; Liu, Minmin; Gao, Faming; Zhang, Jiujun; Zhao, Yufeng
Abstract: The catalytic performance of Pt‐based catalysts for oxygen reduction reactions (ORR) can generally be enhanced by constructing high‐index exposed facets (HIFs). However, the synthesis of Pt alloyed high‐index skins on 1D non‐Pt surfaces to further improve Pt utilization and stability remains a fundamental challenge for practical nanocrystals. In this work, Pd nanowires (NWs) are selected as a rational medium to facilitate the epitaxial growth of Pt and Ni. Based on the different nucleation and growth habits of Pt and Ni, a continuous PtNi alloy skin bounded with HIFs spiraled on a Pd core can be obtained. Here, the as‐prepared helical Pd@PtNi NWs possess high HIF densities, low Pt contents, and optimized oxygen adsorption energies, demonstrating an enhanced ORR mass activity of 1.75 A mgPt −1 and a specific activity of 3.18 mA cm −2, which are 10 times and 12 times higher than commercial Pt/C catalysts, respectively. In addition, the 1D nanostructure enables the catalyst to be highly stable after 30 000 potential sweeping cycles. This work successfully extends bulky high‐indexed Pt alloys to core–shell nanostructures with the design of a new, highly efficient and stable Pt‐based catalyst for fuel cells. Abstract : This work reports a helical Pd@PtNi nanowire with continuous PtNi alloy skin bounded with high indexed facets spiraled on a Pd core. The as‐prepared catalyst demonstrate an enhanced ORR mass activity of 1.75A mgPt ‐1 and a specific activity of 3.18 mA cm ‐2, which are 10 times and 12 times higher than commercial Pt/C catalysts, respectively.